A Qualitative Study on Secondary School Teacher’s Perceptions of Stunting in Majene District, West Sulawesi Province - Sitti Patimah; Sundari Sundari; Andi Imam Arundhana (Amerta Nutrition, 2021)
Background: Stunting remains a major public health problem in Majene, Indonesia. School-based nutrition education is an effective strategy to reduce the prevalence of stunting in all settings. The teachers are the key to implementing the strategy in order to improve the students’ behavior and nutritional status.Purpose: The study aimed to explore the teachers’ perceptions about stunting.Method: A qualitative case-study approach was employed using two focus group discussions in four secondary schools. The study participants were teachers of biology, physical education and health science, and religious subjects or supervisor of school extracurricular activities. A total of 22 teachers were interviewed following the guidelines and were recorded using a camera and tape recorder. The transcription process was done using an inductive-interactive model.Result: The perceptions of teachers about stunting are varied. It might be due to teachers’ knowledge, value, and experiences, which also diverged. One teacher perceived that stunting is a mismatch between the child's weight and age, while another perceived genetics as the main cause. Interestingly, a teacher perceived that stunting is related to religion. Prayer has function as a spirit in creating a mindset towards food and drinks. Likewise, the prevention of stunting is also through worship and prayer during pregnancy. Low cognitive skill and productivity, illness, and detrimental to the state are the common impacts of stunting. In addition, teachers also mentioned that there are several agencies involved in the stunting intervention programs, including BPOM.Conclusion: There were variations of teacher perceptions about stunting definition, causes, impacts, prevention, and implementers of stunting programs.